Special quenching inductor of gyration support rail - ZHOU XIANGCHENG (2016)
The utility model provides a special quenching inductor of gyration support rail, includes a pair of electrically conductive connecting plate, and the one end and the annular effective heating collar of circle of a pair of electrically conductive connecting plate are connected, and a pair of electrically conductive connecting plate forms a closed current loop with effective heating collar, all is equipped with the cooling passage in a pair of electrically conductive connecting plate and the effective heating collar, and effective heating collar constitutes the endless cooling passage with a pair of electrically conductive connecting plate, is equipped with the magnetizer of joint on effective heating collar, the top of effective heating collar is equipped with the installation fixed plate, and one side of installation fixed plate is fixed in on a pair of electrically conductive connecting plate through a pair of fixing support, the below of effective heating collar is equipped with the annular first sprinkling machine of circle, and the installation fixed plate is connected with first sprinkling machine, and effectively heating collar and first sprinkling machine are concentric from top to bottom corresponds the setting, and the end areal distribution of the corresponding work piece of first sprinkling machine has the hole for water spraying. The device compares with current partial sweep mode, and efficiency has improved four to six -tenehs - 10 times, has saved the energy.